Cyber warfare dalam Konflik Modern: Analisis Serangan Stuxnet pada Fasilitas Nuklir Iran - Arianto Arianto (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2025)
Stuxnet is one of the first politically motivated cyberattacks in history. This attack targeted Iran's nuclear facility in Natanz, causing significant setbacks in the country's nuclear program. Iran accused the West, particularly NATO, of orchestrating the attack. Many believe that the United States and Israel were behind it. This paper aims to analyze how Stuxnet impacted Iran and the international community, as well as how cyber warfare has emerged as a new domain of conflict. The method used in this paper is qualitative descriptive through library research. The data used in this study are sourced from books, journals, news articles, and credible, relevant websites. The findings indicate that Stuxnet had a severe impact on Iran and the geopolitical situation at the time. It also highlighted the vulnerabilities of the digital world and their real-world consequences. Furthermore, Stuxnet demonstrated how cyber warfare has emerged as a new domain in modern conflict.